High Gain and High Directive of Antenna Arrays Utilizing Dielectric Layer on Bismuth Titanate Ceramics - Al-Amani, Umar (2012)
A high gain and high directive microstrip patch array antenna formed from dielectric layer stacked on bismuth titanate (BiT)ceramics have been investigated, fabricated, andmeasured. The antennas are designed and constructed with a combination of two-,four-, and six-BiT elements in an array form application on microwave substrate. For gain and directivity enhancement, a layer of dielectric was stacked on the BiT antenna array.We measured the gain and directivity of BiT array antennas with and without the dielectric layer and found that the gain of BiT array antenna with the dielectric layer was enhanced by about 1.4 dBi of directivity and 1.3 dB of gain over the one without the dielectric layer at 2.3GHz. The impedance bandwidth of the BiT array antenna both with and without the dielectric layer is about 500 MHz and 350MHz, respectively, which is suitable for the application of the WiMAX 2.3 GHz system. The utilization of BiT ceramics that covers about 90% of antenna led to high radiation efficiency, and small-size antennas were produced. In order to validate the proposed design, theoretical and measured results are provided and discussed.